2014
DOI: 10.1002/jbio.201300169
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between water loss, mechanical stress, and molecular structure of human stratum corneum ex vivo

Abstract: Proper hydration of the stratum corneum (SC) is important for maintaining skin's vital functions. Water loss causes development of drying stresses, which can be perceived as 'tightness', and plays an important role in dry skin damage processes. However, molecular structure modifications arising from water loss and the subsequent development of stress has not been established. We investigated the drying stress mechanism by studying, ex vivo, the behaviors of the SC components during water desorption from initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 45 publications
(50 reference statements)
5
48
0
Order By: Relevance
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…material). Generally, our Raman assignments correlate with those in the literature [26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46]. The Raman spectrum of the SC is dominated by vibrational bands of its structural proteins, lipids, and tissue water.…”
Section: Resultssupporting
confidence: 74%
“…OH stretching associated with this water arises around 3,420-3,600 cm -1 . The ratio between unbound water and partially bound water has been calculated [26]. …”
Section: Resultsmentioning
confidence: 99%
“…High values of this ratio are indicative of exposed tyrosine while a shift for lower values is related to buried tyrosine. . Figure d shows an exposition of the tyrosine ring after 30 minutes of incubation with trypsin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been recently demonstrated that CRS can differentiate between different water-binding states, including unbound, partially bound and primary bound water [68,69]. The water content in each binding state has been found to vary differently in function of external stimuli, such as humidity and mechanical stress and, remarkably, correlations with structural and organizational changes in lipids and proteins were highlighted [68,70]. This demonstrates the potential of CRS to study the correlation of the skin barrier and hydration status in function of different stimuli.…”
Section: Discussionmentioning
confidence: 99%